The role of urban forests in mitigation of particulate air pollution: Evidence from ground observations in South Korea - Seo, Jihoon; Oh, Hye-Ryun; Park, Doo-Sun R.; Kim, Jin Young; Chang, Dong Yeong; Park, Chan Ryul; Sou, Hong-Duck; Jeong, Sujong (Elsevier BV, 2025)
The effects of forests in mitigating urban air pollution have not been fully evaluated due to limited observational data. This study assesses the role of urban forests in reducing particulate matter (PM) using data from the recently installed ground PM observation network across South Korean forests, known as the Asian Initiative for Clean Air Networks (AICAN). Results show that urban forests are more effective at reducing coarse PM (with PM decrease efficiencies of 4.5 % to 24.4 % for PM2.5-10) than fine PM (1.5 % to 11.4 % for PM0.25-1.0), particularly in summer due to increased biomass growth. The diminished removal effects observed for fine PM may result from elevated physiological activities within forests, which can enhance the accumulation of fine PM. Buffering forests, planted as belts between pollution sources and residential areas, effectively mitigate PM pollution only when sufficiently wide (at least 200 m) and aligned with the prevailing wind direction. Tower measurements reveal PM deposition onto the forest canopy, while fine PM increases through turbulent diffusion under the canopy. This study underscores the importance of urban planning and reforestation strategies in reducing PM levels and highlights the significant role of urban forests in mitigating air pollution.